Finding My Place: An Autoethnographic Exploration of My Experiences as an International Student in Aotearoa New Zealand - Nizvi Farin, Fathima Nusra (Auckland University of Technology, 2025)
This dissertation examines the multifaceted experience of an international student from Saudi Arabia with Sri Lankan background, undertaking a Master of Education in Aotearoa New Zealand. This study utilizes autoethnography as its primary methodological framework, combining personal narrative with cultural analysis to investigate experiences of migration, adaptation, and professional development. Underpinned by a qualitative research paradigm, the study strongly emphasizes subjectivity and reflexivity, which is consistent with interpretivist traditions that place significant importance on an individual's lived experiences. The research utilizes reflective storytelling to explore three primary enquiries: the influence of the initial transition on the sense of belonging, the difficulties encountered in a predominantly non-Muslim society, and the role of the study experience in personal and academic growth.
Keywords: Emotional Well-being; Autoethnography; Migration Challenges; Resilience and Identity; International Student Experience